Micro-assets and portfolio management in the new platform economy. Issue 1 (2nd January 2022) - McKenzie, Monique de Jong
ABSTRACT: Digital labour platforms act as intermediary agents between users and are imbued with the power to determine the rules of interaction within their own digital ecosystem. As the labour market has become increasingly integrated into the platform economy, digital enterprises have been able to use their concentration of power to experiment with new structures of labour regulation and management. The key transformation of labour by platform enterprises is the fragmentation of labour contracts into minute by minute tasks, with noteworthy implications for our understanding of human capital investment in the digital age. As individuals are required to sell their abilities as micro-skills such as photo-tagging and copy editing, long-term human capital investments such as higher education are devalued. These long-term assets are replaced by highly volatile and short-term human capital assets such as reputation scores and platform metrics. This paper will investigate these new forms of human capital, exploring how they are held hostage by platform enterprises to lock users in and structure how labour is practiced in the new digital economy.